SOCIAL MEDIA SEGEMENTATION AMONG UNIVERSITY STUDENTS: A COMPARISON BETWEEN UNIVERSITAS SWADAYA GUNUNG JATI CIREBON AND UNIVERSITAS PADJAJARAN BANDUNG - Nurfalah, Farida; Abdullah, Aceng; Nur Aisyah , Maya (Cirebon Annual Multidiciplinary International Conference (CAMIC), 2024)
Human behavior has evolved in the digital age, and students are no exception. They are now very receptive to technology, particularly social media. This research is aimed at disucssiong how students at Universitas Swadaya Gunung Jati (UGJ) Cirebon and Universitas Padjajaran (Unpad) Bandung divide up on social media; how interested students at UGJ and Unpad in using social media; and what societal difficulties affect students at UGJ and Unpad. A qualitative descriptive research methodology is employed in this study. Utilizing a purposive technique, 12 respondents from UGJ and Unpad were included as the sample. A focus group discussion (FGD) was also held with ten students selected at random. The research found that there aren't many differences between UGJ and Unpad students' social media segmentation when it comes to their usage patterns, media intensity, the purpose of social media for them, the groups they are a part of, and the money they spend on reaching their quotas. 2. The social media platforms that WA, Youtube, Instagram, Facebook, Twitter, Tiktok, Telegram, and Line utilize pique their curiosity in using social media, and UGJ students add podcasts and spotfy. The social media platforms that are most commonly used include WhatsApp, Instagram, Facebook, Twitter, Line, and WA. Conversely, Tiktok, Reddit, Discord, and Telegram are less frequently used, with Telegram being used infrequently among UGJ students. The research found that the social media segmentation of UGJ and Unpad students is not much different, starting from their activities in using social media, media intensity, the function of social media for them, the groups they belong to, and the funds spent on purchasing quotas. 2. Their interest in using social media is also the social media applications used by WA, Youtube, IG, FB, Twitter, Tiktok, Telegram, Line, while UGJ students add Podcast/spotfy. What social media are most frequently used, WA, Youtube, IG, FB, Twitter, and Line, and which ones are rarely used, Tiktok, Reddit, Discord, and Telegram, while for UGJ Students, Telegram. 3. There is a shift in habits from watching TV and reading to playing on cellphones, with opinions of the usage of social media pointing to increased information and social connection with old and new acquaintances. They need to filter the information they receive and be adept at sharing your time because social media has a negative effect on them and makes them erratic, lethargic, and the source of fake news.